Aquaponics vs recirculating aquaculture system: assessing productivity and water use efficiency of native fish species empurau (Tor tambroides) and jelawat (Leptobarbus hoevenii) compared to red hybrid tilapia - Qi-Song Colin, Kiu; Chaiw-Yee, Teoh; Ooi, Ai-Lin (Penerbit Universiti Kebangsaan Malaysia, 2024)
A 3 × 2 (fish species × culture system) factorial design experiment was conducted to compare productivity of empurau (Tor tambroides), jelawat (Leptobarbus hoevenii) and red hybrid tilapia (Oreochromis sp., control) cultured in recirculating aquaculture system (RAS) and aquaponics system. Growth performance, feed conversion ratio (FCR) and survival rate of fish were evaluated, and water quality of all tanks throughout the 70-days experiment was determined. In the present study, FCR of tilapia, empurau and jelawat tended to be lower in aquaponics than RAS, while no significant differences (P>0.05) on weight gain (WG) and specific growth rate (SGR) between RAS and aquaponics for each fish species were observed. Although tilapia had significantly higher WG and SGR, and lower FCR compare to empurau and jelawat, the survival rate of empurau and jelawat were higher than tilapia, regardless of the culture system. Between empurau and jelawat, better growth performance was observed in aquaponics than in RAS. Significantly higher (p<0.05) ammonia and nitrite concentrations were shown in RAS tanks as compared to aquaponics tanks, regardless of the fish species. Jelawat might have wide range tolerance to ammonia as no mortality in both RAS and aquaponics, while tilapia and empurau had higher survival rate in aquaponics than RAS. In summary, aquaponics appears to be a viable approach to enrich variety and improve fish production in an environmentally responsible manner. Therefore, it is plausible to advocate for the use of aquaponics as a sustainable methods of farming native fish species in Malaysia.